Persepsi Mahasiswa yang Kuliah di Surabaya Tentang Keterlibatan Artis Dalam Pilihan Legislatif 2019 Daerah Pilihan Jawa Timur - Iin Erlina Eka Putri; Agnesia Midiana; Shara El Fani; Ridwan Arma Subagyo; Mohammad Alfin Mahbi Awaludin; Agus Machfud Fauzi (Fakultas Ilmu Sosial dan Ilmu Politik, 2019)
The legislative election is an opportunity for artists to get involved in politics. Popularity became the main capital for artists in the five-year political contestation. Although they have no political background, there are not a few artists who continue to advance as legislative candidates from the regional to the national level. This phenomenon has led to various perceptions among students who have an important role in politics. As educated actors students are able to look at, criticize and respond to political phenomena that are happening. However, differences in the background of each student affect the way they see the phenomenon of artist involvement in legislative elections. Therefore this study aims to determine the perceptions of Surabaya students about artists involved in the 2019 legislative choice in East Java. This research uses a descriptive qualitative approach with interview and literature study methods. Research subjects were state and private university students in Surabaya who were determined using cluster sampling techniques. This study uses Daryl Benn's self-perception theory. The results showed that there were various views or perceptions of Surabaya students about the involvement of artists in the 2019 legislative elections for East Java. The difference in perception is caused by the background of the students themselves such as regional origin, experience, and political knowledge